A high-yield procedure for isolation of metaphase chromosomes from root tips of Vicia faba L - Doležel, J; Cíhalíková, J; Lucretti, S (Planta, 1992)
A new method is described for the isolation of large quantities of Vicia faba metaphase chromosomes. Roots were treated with 2.5 mM hydroxyurea for 18 h to accumulate meristem tip cells at the G1/S interface. After release from the block, the cells re-entered the cell cycle with a high degree of synchrony. A treatment with 2.5 μM amiprophos-methyl (APM) was used to accumulate mitotic cells in metaphase. The highest metaphase index (53.9%) was achieved when, 6 h after the release from the hydroxyurea block, the roots were exposed to APM for 4 h. The chromosomes were released from formaldehyde-fixed root tips by chopping with a scalpel in LB01 lysis buffer. Both the quality and the quantity of isolated chromosomes, examined microscopically and by flow cytometry, depended on the extent of the fixation. The best results were achieved after fixation with 6% formaldehyde for 30 min. Under these conditions, 1 · 10(6) chromosomes were routinely obtained from 30 root tips. The chromosomes were morphologically intact and suitable both for high-resolution chromosome studies and for flow-cytometric analysis and sorting. After the addition of hexylene glycol, the chromosome suspensions could be stored at 4° C for six months without any signs of deterioration.